2011
DOI: 10.1002/tea.20440
|View full text |Cite
|
Sign up to set email alerts
|

The missing disciplinary substance of formative assessment

Abstract: We raise concerns about the current state of research and development in formative assessment, specifically to argue that in its concentration on strategies for the teacher, the literature overlooks the disciplinary substance of what teachers and students assess. Our argument requires analysis of specific instances in the literature, and so we have selected four prominent publications for consideration as examples. These, we show, pay little attention to the student reasoning they depict, presume traditional n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
198
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(211 citation statements)
references
References 58 publications
(82 reference statements)
3
198
0
3
Order By: Relevance
“…Science teachers are constantly confronted with students' ideas about scientific phenomenon, including alternative conceptions and misconceptions, and must draw on their understanding of the subject matter to interpret students' ideas and probe for understanding (Coffey, Hammer, Levin, & Grant, 2011;Forbes, Sabel, & Biggers, 2015;Levin, 2013). Research has suggested that this aspect of the work of teaching science is neither intuitive nor straightforward (Nilsson & van Driel, 2010;Otero & Nathan, 2008).…”
Section: Conceptualizing Practice-based Measures Of Content Knowledgementioning
confidence: 99%
“…Science teachers are constantly confronted with students' ideas about scientific phenomenon, including alternative conceptions and misconceptions, and must draw on their understanding of the subject matter to interpret students' ideas and probe for understanding (Coffey, Hammer, Levin, & Grant, 2011;Forbes, Sabel, & Biggers, 2015;Levin, 2013). Research has suggested that this aspect of the work of teaching science is neither intuitive nor straightforward (Nilsson & van Driel, 2010;Otero & Nathan, 2008).…”
Section: Conceptualizing Practice-based Measures Of Content Knowledgementioning
confidence: 99%
“…We find this analogy useful for several reasons. First, the construct of science sensemaking has been well developed [58,59,64,65], and encompasses practices valued by the science education community [62,66,67]. Thus, it can provide a starting point for conceptualizing pedagogical sensemaking, particularly for researchers who are less familiar with the existing PD literature.…”
Section: Pedagogical Sensemakingmentioning
confidence: 99%
“…Los resultados de la investigación educativa en diversas áreas nos permiten identificar el tipo de interacciones formativas que tienen un mayor potencial para involucrar a la mayoría de los estudiantes en trabajo intelectual productivo (Coffey et al, 2011). Algunos autores se refieren a estas interacciones como prácticas docentes que sustentan la enseñanza ambiciosa de la disciplina (Windschitl et al, 2012).…”
Section: La Evaluación Formativa Como Marco De Referencia Y Acciónunclassified